2010
DOI: 10.1016/j.regpep.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

High sucrose intake in rats is associated with increased ACE2 and angiotensin-(1–7) levels in the adipose tissue

Abstract: Sucrose-fed rats, a model of metabolic syndrome, are characterized by insulin resistance, obesity, hypertension, and high plasma levels of triacylglycerols and angiotensin II (Ang II). However, whether tissue renin-angiotensin system (RAS) is altered in metabolic syndrome is unclear. To study this issue, food ad libitum and water (C) or 20% sucrose solution (SC) were given to adult male Wistar rats, for 30 days. Body weight (BW), blood pressure (BP), epididymal adipose tissue (EPI) mass, rate of in vivo fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
1
30
0
1
Order By: Relevance
“…Moreover, we also observed similar levels of Ang II in the eWAT which was again much higher than the reported value available in the literature. 15 The existing method employs time-consuming peptide extraction procedure by HPLC and its detection by RIA is lengthy, costly and poses health risk. Although mass spectrometry is an expensive instrument, it is automated and time-efficient; cost of running samples is low.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we also observed similar levels of Ang II in the eWAT which was again much higher than the reported value available in the literature. 15 The existing method employs time-consuming peptide extraction procedure by HPLC and its detection by RIA is lengthy, costly and poses health risk. Although mass spectrometry is an expensive instrument, it is automated and time-efficient; cost of running samples is low.…”
Section: Resultsmentioning
confidence: 99%
“…Typically regarded as the enzyme that initiates the RAS cascade, renin is an aspartyl-type protease (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) that cleaves angiotensinogen to form the inactive peptide ANG I (Fig. 1).…”
Section: Ras Protein Componentsmentioning
confidence: 99%
“…ANG II and ANG-(1-7) values derived from these methods are typically far higher in plasma (26,33,51,135), kidney (33,110,114), vasculature (48), adipose tissue (33,115), and heart (42) than by RIA, HPLC-RIA, or HPLC-MS methods (Table 1). Indeed, two recent studies quantified mouse renal ANG-(1-7) at Ͼ1,000,000 fmol/g tissue (110) and rat plasma ANG II at Ͼ300,000 pM by HPLC analysis alone (33). Rubio-Ruiz et al (115) reported an ANG-(1-7) concentration of 6,000 pM in serum and Ͼ500,000 fmol/g in adipose tissue from male Wistar rats by capillary electrophoresis.…”
Section: Ras Peptidesmentioning
confidence: 99%
“…Additional studies investigating the ACE2 component of this ‘protective arm’ in adipose tissue have revealed that the expression and activity of this enzyme are regulated by energy status [23, 88, 89]. For example, Gupte et al .…”
Section: The Renin Angiotensin System and The Peripheral Regulatiomentioning
confidence: 99%